(untitled) (Journal of Economic Additions, 2026)
This study explores the synergy between multi-objective programming and intelligent techniques within hybrid models to optimize complex decision-making. Findings indicate that these hybrid systems improve decision quality by effectively balancing conflicting objectives and navigating high-uncertainty environments. Furthermore, intelligent algorithms enhance the precision and flexibility of outcomes. The research advocates for deeper integration of AI with mathematical modeling, improved data quality, and the expanded deployment of hybrid frameworks in strategic decision-making. Jel Classification Codes: C61, C45, C63, C44.